Periodic variations in time of atmospheric radioactive nanoparticles - V.V. Dyachkov; Yu.A. Zaripova; A.V. Yushkov; A.L. Shakirov; M.T. Bigeldiyeva; K.S. Dusebayeva; K.E. Abramov (Physical Sciences and Technology, 2018)
In the article the authors present the data of periodic variations in time of radon emanations in the ground layer of the atmosphere, which were measured for the period from January 1 to August 3, 2016. Harmonics of diurnal, 4-day and longer periods are revealed. The authors interpreted the 4-day variations, which can occur due to "lunar tides", that is, from soil uplifts due to the increase in gravitational tidal forces. The mechanism of radon emanation to the Earth's surface is complex. The mechanism of radon emanation to the Earth's surface is complex. In particular, the transportation of radon from the inner surfaces of the earth's crust is carried out by the diffusion of aerosols onto the surface, to which the radon atoms coagulate, due to electrostatic attraction. Such radioactive aerosol nanoparticles located in the surface layer of the atmosphere have the greatest impact on the risks of cancer, since the probabilities of their settling on the lung tissues are several orders of magnitude higher than the radon itself in the atomic form.